Systematic review on community-based interventions targeting prevention of overweight and obesity in children and adolescents - Santamaria, Júlia; Mühlberger, Nikolai; Schmid, Daniela; Kuchin, Igor; Suzumura, Erica A.; Ayad, Nardeen; Hsieh, Yuli Lily; Tuohy, Kieran; Laxy, Michael; Siebert, Uwe; Jahn, Beate (Frontiers in Public Health, 2025)
BackgroundWith increasing obesity rates, community-based interventions (CBIs) have gained attention as more evidence suggests that the environment has a significant impact on individuals’ behaviors. We aimed to conduct a systematic review of CBIs for preventing overweight/obesity in children and adolescents.Subject and methodsWe searched PubMed (January 2011–December 2024) for studies evaluating CBIs for the prevention of overweight and obesity. We included controlled interventional studies that reported weight-related outcomes. The assessment of risks of bias of the included studies was performed using the Cochrane Collaboration tool. Results are reported in systematic evidence tables, including information on main study characteristics and effect sizes.ResultsA total of 2,724 articles were retrieved, of which 37 publications representing 28 projects from seven world regions were included for review. Most of the interventions targeted children. Reported intervention effects ranged from none to small effects. A beneficial intervention effect was observed in 11 out of 16 studies that calculated the intervention effect for BMI z-score and in seven out of nine studies for the prevalence of overweight/obesity. Effect sizes ranged from −0.26 to −0.03 for the BMI z-score and up to an adjusted odds ratio of 0.65 in the intervention group compared to the control group, with respect to the prevalence of overweight/obesity. The risk of bias of the studies was moderate to high.ConclusionOverall, our study found inconclusive evidence on the benefits of CBIs. While creating health-promoting environments can influence population-wide nutrition and physical activity behaviors by making healthy choices more accessible, methodological challenges exist to accurately capture the true effects of CBIs.